METRIZABILITY ON TOPOLOGICAL SIMPLE ROUGH GROUPS - P. TAMILARASI; R. SELVI (Utilitas Mathematica, 2025)
In this paper, we focus on the concepts of rough pseudonorm and metrizability in topological simple rough groups. Further, we discuss some results related to these concepts. In particular, we explore the interplay between rough pseudonorms and metrizability, and also highlighting the necessary and sufficient condition to ensure a topological simple rough group is metrizable. These findings contribute to a deeper understanding of the structural dynamics of topological simple rough groups.